Associations between early childhood caries, malnutrition and anemia: a global perspective - Morenike Oluwatoyin Folayan (BMC Nutrition, 2020)
Abstract Background Malnutrition is the main risk factor for most common communicable diseases. The aim of this study is to determine the relationship between country-level prevalence of early childhood caries (ECC), malnutrition and anemia in infants and preschool children. Methods Matched country-level ECC, malnutrition and anemia prevalence were generated from databases covering the period 2000 to 2017. Multivariate general linear models were developed to assess the relationship between outcome variables (prevalence of stunting, wasting, overweight, and anemia) and the explanatory variable (ECC prevalence) adjusted for gross national income per capita. Adjusted regression coefficients (B) and partial eta squared were computed. Results The mean (standard deviation (SD)) ECC prevalence was 23.8 (14.8)% for 0–2 year-olds and 57.3 (22.4)% for 3–5-year-olds. The mean (SD) prevalence of wasting was 6.3 (4.8)%, overweight 7.2 (4.9)%, stunting 24.3 (13.5)%, and anemia 37.8 (18.1)%. For 0–2-year-olds, the strongest and only significant association was between the prevalence of ECC and overweight (η2 = 0.21): 1 % higher ECC prevalence was associated with 0.12% higher prevalence of overweight (B = 0.12, P = 0.03). In 3–5-year-olds, the strongest and only significant association was between the prevalence of ECC and anemia (η2 = 0.08): 1 % higher prevalence of ECC was associated with 0.14% lower prevalence of anemia (B = − 0.14, P = 0.048). Conclusion Country-level prevalence of ECC was associated with malnutrition in 0–2-year-olds and with anemia in 3–5-year-olds. The pathway for the direct relationship between ECC and overweight may be diet related. The pathway for the inverse relationship between ECC and anemia is less clear and needs further investigations.